Impact of time to endovascular reperfusion on outcome differs according to the involvement of the proximal MCA territory. (30th August 2017) - Hedderich, Dennis M; Boeckh-Behrens, Tobias; Friedrich, Benjamin; Wiestler, Benedikt; Wunderlich, Silke; Zimmer, Claus; Fischer, Urs; Kleine, Justus F; Kaesmacher, Johannes
Abstract : Background: The time interval between symptom onset and reperfusion is a major determinant of the benefit of endovascular therapy (ET) and patients' outcome. The impact of time may be attenuated in patients with robust collaterals. However, not all regions in the middle cerebral artery (MCA) territory have access to collaterals. Purpose: To evaluate if the involvement of the poorly collateralized proximal MCA territory has an impact on the degree of time dependency of patients' outcome. Methods: Patients with MCA occlusions treated with ET and involvement/sparing of the proximal striatocapsular MCA territory (SC+/SC−, each n=97) were matched according to their symptom onset to reperfusion times (SORTs). Correlation and impact of time on outcome was evaluated with strata of SC+/SC− using multivariate logistic regression models (LRMs), including interaction terms. Discharge National Institute of Health Stroke Scale (NIHSS-DIS) score <5 and discharge modified Rankin Scale (mRS-DIS) score ≤2 were prespecified outcome measures. Results: A stronger correlation between all outcome measures (NIHSS-DIS/ΔNIHSS/mRS-DIS) and SORTs was found for SC+ patients than for SC−patients. SORTs were significant variables in LRMs for mRS-DIS score ≤2 and NIHSS-DIS score <5 in SC+ but not in SC− patients. Interaction of SC+ and SORTs was significant in LRMs for both endpoints. Conclusion: Time dependency of outcome after ET is more pronounced if parts of the proximal MCA territory are affected. This may reflect the lack of collateralization in the striatocapsular region and a more stringent cell death with time. If confirmed, this finding may affect the selection of patients based on different time windows according to the territory at risk.